2018
DOI: 10.1186/s12880-018-0285-1
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of a feature-based algorithm for 3D-3D registration of CT angiography to cone-beam CT for endovascular repair of complex abdominal aortic aneurysms

Abstract: BackgroundA crucial step in image fusion for intraoperative guidance during endovascular procedures is the registration of preoperative computed tomography angiography (CTA) with intraoperative Cone Beam CT (CBCT). Automatic tools for image registration facilitate the 3D image guidance workflow. However their performance is not always satisfactory. The aim of this study is to assess the accuracy of a new fully automatic, feature-based algorithm for 3D3D registration of CTA to CBCT.MethodsThe feature-based algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Furthermore, we can also continuously position the location in real time during the operation, which is favourable for the surgeon being able to protect the patient's nerve function intraoperatively. At present, CT three-dimensional angiography has also been widely used in patients with intracranial aneurysms, and has improved the positioning accuracy and enhanced the nerve function of patients (15)(16)(17)(18). The above reports support the results of our study, which showed that neuronavigation combined with CT three-dimensional angiography can significantly improve the neurological function and shorten the hospital stay time in intracranial distal aneurysm surgery.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, we can also continuously position the location in real time during the operation, which is favourable for the surgeon being able to protect the patient's nerve function intraoperatively. At present, CT three-dimensional angiography has also been widely used in patients with intracranial aneurysms, and has improved the positioning accuracy and enhanced the nerve function of patients (15)(16)(17)(18). The above reports support the results of our study, which showed that neuronavigation combined with CT three-dimensional angiography can significantly improve the neurological function and shorten the hospital stay time in intracranial distal aneurysm surgery.…”
Section: Discussionsupporting
confidence: 84%
“… 25 Another improvement would be the use of algorithms to correct for vessel displacement (mostly iliac artery) after insertion of stiff guidewires, sheaths, and stent delivery devices to ensure a one to one 3D roadmap that continuously corrects for anatomic vessel changes. 26 33 With algorithms like these, the user can rely more on image fusion during the procedure. The need for large contrast volumes in order to navigate might be completely eliminated, and only small volumes of nephrotoxic contrast would be needed for image fusion validation.…”
Section: Discussionmentioning
confidence: 99%
“…Current image fusion systems are designed as hardware-based systems that match the coordinate system of the C-arm and operation table, with preoperative CTA. Due to exponential growth of computer power, it is now possible to automate such tasks and change from hardwarebased to image-based registration [15][16][17][18][19]. The aim of this experimental study was to assess the feasibility and accuracy of automated image-based 2D-3D registration, which automatically fuses preoperative CTA and a single-shot intraoperative fluoroscopy, based on vertebral column matching.…”
mentioning
confidence: 99%